The hormone-like myokines irisin as novel biomarker for cardiovascular risk stratification - Berezin, A. A.; Myrnyi, D. P.; Myrnyi, S. P.; Berezin, A. E.; Березін, Олександр Євгенійович (India: Jadoun Science Publishing Group, 2021)
As a skeletal muscle cell-derived protein, Irisin regulates glucose and lipid metabolism, mitochondrial function, myogenesis, switching white adipocytes to brown fat-like cells, and thermogenesis and energy expenditure. The descriptive review aim is to summarize the knowledge regarding irisin as novel molecular mediators of energy metabolism of remote tissue with promising diagnostic and predictive values for CV risk in connection with a presence of metabolic conditions. The following database were used for searching of life science and biomedical information MEDLINE, the Web of Science, Medline (PubMed), the Cochrane Central, and EMBASE English publications to satisfy the keywords of this investigation. Lowered concentrations of irisin were found in the patients with known CV disease including heart failure, Type 2 Diabetes Mellitus (T2DM), but the levels of circulating irisin were increased in obesity and pre-diabetes patients compared to healthy volunteers. In the general population, low levels of irisin have closely predicted T2DM, atherosclerosis, and coronary artery disease. Circulating levels of irisin in patients that have incident Heart Failure (HF) with reduced ejection fraction were related to the severity of the disease and can be a marker of cardiac cachexia. In contrast, in acute HF patients increased the levels of irisin in peripheral blood positively related to a one-year CV mortality rate. Large clinical studies are needed to determ the predictive role of irisin in the natural evolution of CV disease including HF, myocardial infarction, and cardiac cachexia.
Keywords: Cardiovascular disease; Cardiovascular risk; Myokines; Secretomics; Type 2 diabetes mellitus